Model Bimbingan Pendidikan Agama Islam Bagi Anak Tuna Netra: Children with special needs, Blind, Islamic Guidance - Difa’ul Husna; Harmita; Muhammad Lutfi Nur Fauzi; Putri Fahma Fiddini; Defrian Riski Muncar Atmana (Jurnal Penelitian Multidisiplin, 2022)
Children with special needs have many kinds of classifications, one of which is children with special needs who are blind. Researchers use literature research methods and use a qualitative approach, not forgetting to develop reading materials researchers also look for good sources of information from the media such as journals, articles as material for developing data in research. The purpose of this study was to find out and obtain knowledge about methods and models of Islamic Religious Education guidance for blind children which later can also become a reference and can be applied to readers in applying Islamic Religious Education guidance methods and models for children with special needs who are blind. While the results of the study contain the characteristics and disorders of children with special needs who are blind and the methods used in Islamic Religious Education guidance for blind children using lecture, question and answer and demonstration methods.